Identification of anise (Anisum vulgare Gaertn.) herbs by morphological and anatomical characteristics - S. V. Kolisnyk; T. M. Gontova; U. A. Umarov; K. R. Hordiei (Zaporozhye State Medical University, 2021)
The fruits of anise contain different classes of biologically active compounds, due to which they have antidepressant, antiperoxidant, antidiabetic effect; extracts of this plant have an antibacterial effect. Professional literature lacks information on the chemical composition of anise herbs and prospects for their use in medicine. The aim of the work is to study of the morphological and anatomical structure of the aboveground organs of anise and to establish of macro- and microscopic diagnostic characters necessary for the identification of the plant raw materials. Materials and methods. Anise herbs consisting of stems, leaves flowers, and unripe fruits were used for the study. Fresh and dried raw materials were macroscopically analyzed with the naked eye and using a magnifying glass (×10). Studies of transverse and longitudinal sections, epidermis and surface preparations were performed using conventional techniques: with microscopes MBS 9, MS 10 (glasses ×5, ×10, ×15, lenses ×10, ×40), Micromed XS-4130 (eyepiece WF15X, lenses ×40/0.65, ×10/0.25) with a photomicrographic attachment. The micrographs were taken with Samsung PL50 camera. Results. As a result of the macro- and microscopic analysis, diagnostic properties of anise herbs were established. Conclusions. It is for the first time that macro- and microscopic characteristics of anise herbs were studied, which confirms the identity of raw materials. The obtained results will be used for the development of domestic normative documentation on anise herbs raw materials.